Development of Web-Based Retribution Payment Report Information System: A Case Study of Dorowati Market, Kebumen - Priyo Prasojo, Unggul; Fadjeri, Akhmad (Journal of Engineering, Electrical and Informatics, 2025)
Traditional markets remain central to community economic activity, yet many still rely on manual systems for managing retribution payments. At Dorowati Market in Kebumen, Indonesia, payment recording is conducted using paper-based control cards and receipts, leading to frequent data loss, reporting delays, and administrative inefficiencies. These challenges highlight the urgent need for a digital solution to streamline retribution management and improve service delivery. This study aims to develop a web-based information system for market retribution payment reporting to assist market officers in managing transactions, trader data, and financial reports more effectively. The research employs a Research and Development (R&D) approach using the Waterfall model, encompassing planning, modeling, construction, deployment, and maintenance stages. System modeling was conducted using Unified Modeling Language (UML) diagrams and Entity-Relationship Diagrams (ERD) to visualize user interactions and database structure. The system was successfully implemented and evaluated by 30 respondents using a four-point Likert scale. The average score was 3.76, indicating a high level of user satisfaction. The highest-rated statement This system is suitable for broader implementation in other traditional market received a score of 3.90. These results demonstrate that the system enhances operational efficiency, reduces data errors, and supports transparent retribution management.